Influência da variação de parâmetros da técnica de fusão seletiva a laser na microestrutura e dureza da liga reciclada Al-Fe-Cr-Ti formadora de fase quasicristalina - Micheloti, Leandro César (Universidade Federal de São Carlos, 2020)
Selective laser melting (SLM) is an additive manufacturing technique that has attracted increasing interest due to the possibility of creating products with complex geometries and customizable density, which could not be produced by traditional processes, such as machining and casting. This technique also allows the achievement of high cooling rates during processing (~105 K/s), which favors the formation of metastable phases. Numerous parameters influence the parts produced by SLM, including power, speed, and the type of material being processed. Quasicrystalline alloys have the ability to precipitate the quasicrystalline (QC) phase under certain processing conditions. The QC phase is a metastable phase characterized mainly by presenting high hardness and brittleness, which requires high cooling rates to precipitate and is usually only obtained in powders and ribbons. SLM is a promising technique for quasicrystalline alloys due to the high cooling rates that are achieved, allowing the formation of the QC phase in bulk products. When the QC phase precipitates in aluminum alloys, it acts as a reinforcement phase of the ductile matrix α-Al, increasing the mechanical strength at high temperatures and the wear resistance of the alloys. Applications in molds and parts for automotive and aeronautical engines are some examples of where these alloys can be applied. The production of quasicrystalline alloys has been carried out using pure elements, however, it is well known the importance of using recycled materials. Taking these considerations, the aim of this work was to investigate the influence of some SLM parameters on the microstructural, thermal, and mechanical characteristics of the recycled quasicrystalline phase-former Al95Fe2Cr2Ti1 alloy. The effects of scanning speed, hatching, sample size, and heating substrate were evaluated regarding to finishing surface, the morphology of the melting pools, content and morphology of the quasicrystalline phase formed and also in the microhardness of the samples. The parts produced were characterized by X-ray diffraction, differential scanning calorimetry, optical microscopy, scanning electron microscopy, density, and microhardness. The results indicated the presence of the quasicrystalline phase in all samples produced by SLM. The density of the samples was not significantly changed with the tested parameters. Higher content of QC phase was obtained for samples produced with higher scanning speed. The morphology of the melt pools was influenced by both scanning speed and hatching. The surface cracks were more evident in the samples constructed with a larger size, however, the increase in the substrate temperature indicated an alternative to reduce this type of defect.
Influence of selective laser melting parameter variations on the microstructure and hardness of a recycled Al–Fe–Cr–Ti quasicrystal-forming alloy
Keywords: Fusão seletiva por laser; Manufatura aditiva; Ligas de alumínio; Quasicristais; Reciclagem; Laser powder bed fusion; Additive manufacturing; Aluminum alloys; Quasicrystals; Recycling; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA; 9. Indústria, Inovação e Infraestrutura